Technology Acceptance Behavior and Feedback Loop: Exploring Reverse Causality of TAM in Post-COVID-19 Scenario - Ishaq, Erum; Bashir, Sajid; Zakariya, Ramsha; Sarwar, Aisha (Frontiers in Psychology, 2021)
In this study, we considered the reverse causality of the technology acceptance model, specifically in the post-COVID-19 scenario. We propose a theoretical model that considers the impact of technology acceptance behaviors after COVID-19 over the beliefs of a user in terms of perceived ease of using technology and its usefulness. More specifically, we suggested that acceptance of technology post-COVID-19 may have influenced many technology-related individual factors such as computer efficacy, mastery experience, and self-regulated learning of users, while using technology that in turn may have affected beliefs of users about ease of using technology. Such an effect is ultimately reflected in the belief of technology usefulness and favorable post-COVID-19 attitude of users toward using technology. We further extend our model to identify mastery orientation of individuals that may moderate the relationship between technology acceptance behaviors and favorable attitude toward using technology in the post-COVID-19 scenario. Both practical and theoretical implications of this perspective are discussed.